ChemInform Abstract: FeCl3·6H2O‐Catalyzed Mukaiyama‐Aldol Type Reactions of Enolizable Aldehydes and Acetals. Issue 9 (March 2015) - Rodriguez‐Gimeno, Alejandra; Cuenca, Ana B.; Gil‐Tomas, Jesus; Medio‐Simon, Mercedes; Olmos, Andrea; Asensio, Gregorio
Abstract A general procedure for the title condensation of dimethylacetals derived from enolizable aldehydes with silyl enol ethers is developed using FeCl3 as the catalyst.